Implementation of the Mahyani Rehab Program by Baznas in an Effort to Overcome Housing Poverty in Bugis Village, Taliwang District, West Sumbawa Regency - Martina Wati; Busaini, Busaini (Future Techno-Science, 2025)
This study aims to describe the implementation of the MAHYANI Rehab Program by BAZNAS as an effort to overcome housing poverty in Bugis Village, Taliwang District, West Sumbawa Regency. The approach used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study indicate that the implementation of the program involves data collection of prospective aid recipients, verification of house conditions, and distribution of aid with funding sources originating from zakat, infak, and sedekah (ZIS). This program has encouraged the improvement of uninhabitable houses to be more suitable and comfortable, such as replacing dirt floors with permanent floors, repairing the structure of stilt houses with stronger materials, and building permanent houses made of bricks. This program not only provides decent housing for the poor, but also reflects the principles of social justice and concern that are in line with Islamic values. The positive impacts of this program include improving the quality of life, reducing the number of uninhabitable houses, and creating public awareness of the importance of adequate housing.